Pilot scale microfiltration - coagulation for treatment of retention pond water. - Saed, Katayon; Megat Mohd Noor, Megat Johari; Abdullah, Abdul Ghani Liew; Salim, Mohd Razman; Hiroshi, Nagaoka; Hidenori, Aya (Taylor & Francis, 2004)
An evaluation of two commonly used coagulants, alum and ferric chloride was conducted to treat retention pond water using microfiltration. To determine the effectiveness of these coagulants in removing turbidity, color, and total suspended solids two different sets of the experiments were performed. Preliminary test was carried out to evaluate the optimum dosages of coagulants. Optimum turbidity removal was achieved with a 4 and 20 mg/L dosage for ferric chloride and alum, respectively. Generally, coupling microfiltration with coagulation using both alum and ferric chloride exhibited excellent effectiveness for turbidity, color, and total suspended solids removal. The efficiency for alum and ferric chloride for turbidity removal were 96 and 98%, respectively, which was greater than 89% removal using microfiltration alone. Furthermore, microfiltration only demonstrated 81 and 83% removal efficiency for color and total suspended solids removal, respectively. However, microfiltration–coagulation using alum and ferric chloride resulted about 83 and 93% color removal, and 92 and 94% total suspended solids removal, respectively.